2008
DOI: 10.1177/0146167208328063
|View full text |Cite
|
Sign up to set email alerts
|

Appearing Socially Competent: The Effects of a Friend's Presence on the Socially Anxious

Abstract: As hypothesized, while introducing themselves to another person via video, participants high in social anxiety appeared more socially competent with a friend present than when alone. We also examined three potential explanations for this effect and found that while sharing information about themselves on video, most participants high in social anxiety were verbally prompted by their friends. Furthermore, on an open ended question, participants high in social anxiety expressed less negative self-focused thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Because we wanted to examine people who were either high or low in social anxiety, those who scored in the top and bottom tertiles on the pretest were recruited to participate. This strategy of selecting participants has been used in previous research (e.g., Pontari, 2009). Scores on this version of the scale could range from 15 to 75 (LSAs:…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we wanted to examine people who were either high or low in social anxiety, those who scored in the top and bottom tertiles on the pretest were recruited to participate. This strategy of selecting participants has been used in previous research (e.g., Pontari, 2009). Scores on this version of the scale could range from 15 to 75 (LSAs:…”
Section: Methods Participantsmentioning
confidence: 99%
“…Pontari (2009) found that, when introducing themselves to a stranger, socially anxious people appeared more socially competent and experienced fewer negative self-focused thoughts with a close friend present than when alone. Similarly, the clinical literature documents the benefits (less distress and physiological arousal) of having ''safe people'' present (like friends) for those with certain anxiety disorders like panic disorder (Carter, Hollon, Carson, & Shelton, 1995).…”
mentioning
confidence: 90%
“…Taken together, findings (e.g., Arbeau et al, 2012;Pontari, 2009;Teachman & Allen, 2007) suggest that not using social surrogates at all or using them too much may prevent young adolescents from using these peers to enrich their social experiences and enhance positive feelings about themselves. Thus, relative to young adolescents who use social surrogates in moderation, young adolescents who report low and high use of social surrogates may reap fewer social and psychological benefits.…”
Section: Social Surrogacymentioning
confidence: 96%
“…One possible explanation for these findings is that the implications of social surrogate use depend on the extent to which children and adolescents recruit and use their peers in social situations. For example, in one study, Pontari (2009) found that having a friend offer subtle verbal prompts led socially anxious young adults to feel less anxious and appear more socially competent while they interacted with a stranger relative to when they faced the social interaction alone. Although not tested in her study, Pontari speculated that having friends dominate conversations could be counterproductive by leading socially anxious persons to remain passive and wary in social settings.…”
Section: Social Surrogacymentioning
confidence: 99%
“…More-recent research has also shown that socially anxious individuals around close friends are likely to engage in more relationship-promoting behaviors and are seen as more socially competent (Pontari, 2009). However, Baker & McNulty (2010) found that shyness was related to lower levels of relationship self-efficacy and marital relationship satisfaction, with self-efficacy mediating the effect.…”
Section: Behaviormentioning
confidence: 99%